EKSPLORING JAMBI CULTURAL ELEMENTS IN DEVELOPING MATHEMATICS QUESTIONS THAT MEASURE THE COGNITIVE PSYCHOLOGY OF JUNIOR HIGH SCHOOL STUDENTS: Jambi, Indonesia - Caesarani, Nabila Nasywa; Kamid; Yelli Ramalisa (Jurnal Math-UMB.EDU, 2026)
This study was motivated by the importance of integrating local culture into mathematics learning and developing assessment instruments that can measure students’ cognitive psychology, particularly critical thinking skills. The objective of this study was to develop mathematics problems based on Jambi cultural elements and to analyze junior high school students’ critical thinking skills as part of cognitive psychology. This study employed a Research and Development (R&D) method using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The subjects of this study were ninth-grade students of Junior High School 4 Jambi City. Data were collected through interviews, tests, and questionnaires. The developed instrument consisted of ten mathematics problems based on Jambi cultural contexts and six indicators of critical thinking, namely interpretation, analysis, inference, evaluation, explanation, and self-regulation. The results showed that the developed instrument met the validity and reliability criteria. The validation results indicated that the material aspect obtained a score of 86.4% and the design aspect obtained 89.8%, both categorized as very valid. The reliability test using Cronbach’s Alpha showed a value of 0.743, indicating that the instrument had sufficient reliability. The field test results showed that students’ critical thinking skills reached an average score of 70.1%, which is categorized as high. These findings indicate that mathematics problems based on Jambi cultural elements are feasible and effective to be used as an instrument to measure students’ critical thinking skills in mathematics learning. Keywords: Cognitve Psychology; Critical Thinking; Jambi Culture; ADDIE; SPLDV